2016
DOI: 10.1016/j.wneu.2015.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatments for Chronic Subdural Hematomas: A Comprehensive Systematic Review

Abstract: This comprehensive, best evidence-based, quantitative, systematic review indicates that the use of a closed system drainage after burr-hole evacuation reduces the rate of recurrences but has no other significant differences. The findings also suggest that: (1) treatment with twist drills is equivalent to that with burr holes; (2) the postoperative bed header in the elevated position might reduce the length of hospital stay; (3) irrigation of the subdural space with thrombin solution in patients with high risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
73
1
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(85 citation statements)
references
References 79 publications
3
73
1
8
Order By: Relevance
“…[35] Previous studies have reported that corticosteroids, angiotensin converting enzyme inhibitors, tranexamic acid may be adjunctive to surgery, or even as a monotherapy for CSDH treatment. [2,6,7] Nonetheless, there are various surgical intervention and drug options for patients with CSDH, achieving a clinically efficient permanent cure is still far out of reach, and no explicit mechanism can explain this situation so far, we have known that high- and mixed-density of hematoma, leukemia, chronic renal failure, liver diseases are the risk factors for CSDH recurrence. [8] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[35] Previous studies have reported that corticosteroids, angiotensin converting enzyme inhibitors, tranexamic acid may be adjunctive to surgery, or even as a monotherapy for CSDH treatment. [2,6,7] Nonetheless, there are various surgical intervention and drug options for patients with CSDH, achieving a clinically efficient permanent cure is still far out of reach, and no explicit mechanism can explain this situation so far, we have known that high- and mixed-density of hematoma, leukemia, chronic renal failure, liver diseases are the risk factors for CSDH recurrence. [8] …”
Section: Introductionmentioning
confidence: 99%
“…The angiotensin-converting enzyme inhibitors have been found to inhibit the development of immature and new blood vessels in the neomembrane of hematoma. [7] Although previous studies have reported that corticosteroids and tranexamic acid may be beneficial, the evidences remain inadequate. [1,911] Recently, atorvastatin has been reported to be effective to CSDH treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have reported on the prognosis of CSDH patients with or without frailty. Furthermore, most of the previous studies on CSDH focused on surgical method and recurrence reduction, and did not investigate the prognosis of CSDH . Previous studies have shown that age, presence of dementia and the severity of neurological symptoms on admission are correlated with the prognosis of CSDH patients .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, most of the previous studies on CSDH focused on surgical method and recurrence reduction, and did not investigate the prognosis of CSDH. [13][14][15] Previous studies have shown that age, presence of dementia and the severity of neurological symptoms on admission are correlated with the prognosis of CSDH patients. [1][2][3][4] The present study showed that frailty was associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…aSDH is often the result of severe acute trauma, while for patients with cSDH the trauma, if present, has usually occurred several days to weeks prior to manifestation and is often relatively modest. 2 Advanced age and other factors leading to reduced brain volume, for example, alcohol overuse, increase an individual's risk of cSDH. Use of antithrombotic drugs, mainly vitamin K antagonists (VKAs), has also been associated with increased risk of cSDH.…”
Section: Introductionmentioning
confidence: 99%